Special tax regimes in Latin America and the Caribbean: Compliance, social protection, and resource misallocation - Oliver Azuara; Rodrigo Azuero; Mariano Bosch Mossi; Jesica Torres (Inter-American Development Bank (IDB), 2019)
Simplified tax regimes reduce both tax rates and compliance costs for small firms. On the one hand, these regimes increase the number of businesses formally registered and have the potential of also expanding the safety net when they subsidize the contributions to social security of workers in micro firms. On the other hand, they likely incentivize tax evasion due to the discontinuities in the tax schedule they introduce, and distort several micro-level margins, distortions which potentially cumulate into lower levels of aggregate productivity and GDP. In this paper, we exploit data from household surveys and administrative records for Peru, Brazil, and Mexico to examine the likely effect of special regimes on tax revenues, social protection, and resource misallocation. We find bunching of firms around the eligibility threshold of various tax regimes in Peru. This can be due to misreporting to tax authorities or to firms limiting their size to enjoy the benefits of the special tax regimes. In Brazil, we document how the introduction of a special tax regime benefiting the self-employed might have generated incentives for workers to register as entrepreneurs. Finally, in Mexico we find suggesting evidence showing how the introduction of a new special tax regime for small businesses in 2014 might have led to an increase in the number of employers contributing to the social security of their employees and in the number of self-employed making voluntary contributions to social protection. In all these instances we do not quantify exact causal effects, but we present instead descriptive evidence undoubtedly helpful to direct future research.
Keywords: L11; L51; J8; H26; H30; 330; Firm size; productivity; labor regulation; tax evasion and avoidance; general fiscal policies